Preparation method and application of In2O3 / g-C3N5 heterojunction material
The preparation of In2O3/g-C3N5 heterojunction material was solved by hydrothermal method and high-temperature calcination, and the problems of high recombination rate and wide band gap of In2O3 and g-C3N4 photocatalytic materials were solved, and the photocatalytic activity was achieved and the efficient degradation of environmental pollutants.
Patent Information
- Application Number
- CN202411857400.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing In2O3 and g-C3N4 photocatalytic materials have rapid recombination of photogenerated electron-hole pairs and a wide band gap, which limits their photocatalytic activity, especially in terms of solar light utilization and environmental pollutant degradation efficiency.
The In2O3/g-C3N5 heterojunction material was prepared by hydrothermal method and high-temperature calcination method. Through the dislocation energy band structure between In2O3 and g-C3N5, the transmission space of photogenerated carriers was constructed, and the efficiency of photogenerated electrons and holes was promoted. Separate and expand the light utilization rate through the efficient visible light response characteristics of g-C3N5.
It significantly improves the photocatalytic activity, especially in removing environmental pollutants such as rhodamine B, methylene blue, methyl orange, etc., which shows efficient degradation effects, improving the overall performance of the photocatalyst.
Smart Images

Figure CN119303613A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of heterojunction photocatalytic materials and specifically relates to an In 2 O 3 / gC 3 N 5 Preparation method and application of heterojunction materials. Background Art
[0002] With the rapid development of human civilization, global energy crisis and environmental pollution have gradually emerged. Green energy technology has become an urgent need to reduce the use of fossil fuels and reduce the generation of pollutants. Photocatalytic technology is considered to have great potential because it can directly utilize solar energy and can be applied to water decomposition to produce hydrogen, CO 2 Reduction, degradation of organic pollutants, promotion of organic synthesis and other fields. Photocatalysts are the core of photocatalytic technology. Many semiconductor materials such as TiO 2 、CdS、ZnO、BiVO 4 and gC 3 N 4 However, single semiconductor materials have some disadvantages, such as the tendency of photogenerated electron-hole pairs to recombine quickly instead of participating in photocatalytic reactions, which limits their photocatalytic activity.
[0003] In order to inhibit the recombination of electron-hole pairs and improve the photocatalytic activity, constructing heterojunction photocatalytic materials has become a promising method. Heterojunction photocatalytic materials can be divided into type II heterojunction, Schottky type heterojunction, Z type heterojunction and S type heterojunction according to the energy band structure of adjacent materials. These heterojunction materials can effectively inhibit the recombination of electron-hole pairs and improve the overall photocatalytic activity of the material, becoming an important branch of the photocatalyst family.
[0004] In 2 O 3 Indium oxide is an n-type semiconductor material that shows great application potential in the field of photocatalysis due to its unique electronic structure and optical properties. 2 O 3 It has high electron mobility and good visible light response, which enables it to effectively transport electrons during photocatalysis, thereby improving the photocatalytic efficiency. 2 O 3 There are also some limitations, such as the high recombination rate of photogenerated electron-hole pairs, which limits its photocatalytic performance.
[0005] In addition, carbonitrides composed of carbon and nitrogen are a kind of metal-free conjugated polymer materials that have gradually attracted the attention of researchers. 3 N4 Two-dimensional materials have been the most studied and have achieved fruitful results. 3 N 4 There are also some inherent defects, such as its wide band gap of about 2.7 eV, which makes it only absorb a small range of visible light, greatly reducing the utilization rate of sunlight. It is reported that by properly adjusting the ratio of carbon and nitrogen elements in carbon-nitrogen compounds, such as increasing the nitrogen content or forming carbon vacancies, the material can absorb light with lower energy, that is, expand to the visible light region. 3 N 5 This new type of nitrogen-rich carbon-nitrogen compound is composed of one triazole and two triazine molecules connected by azo.
[0006] In 2 O 3 Combining In with carbon and nitrogen compounds to form heterojunction photocatalytic materials is an effective way to overcome the above defects. Professor Xue Can's research group at Nanyang Technological University (10.1016 / j.apcatb.2013.10.029) 2 O 3 Nanocrystalline wafers grown in situ on gC 3 N 4 On the sheet, the obtained In 2 O 3 / gC 3 N 4 Hybrid structure H 2 Generation and CO 2 The photocatalytic activity of gC was significantly improved. 3 N 4 andIn 2 O 3 The interfacial transfer of photogenerated electrons and holes between the two leads to effective charge separation on the two parts. The research group of Professor Liu Chunming of Taipei University of Technology (10.1016 / j.colsurfa.2024.135340) 2 O 3 and tubular gC 3 N 4 The composite formed a heterojunction composite material, and the degradation rates of tetracycline under sunlight and visible light were 100% and 90% respectively within 160 minutes. 2 O 3 and boron-doped gC 3 N 4The composite can degrade 90% of tetracycline hydrochloride within 3 hours, and also shows high photocatalytic degradation activity for NO. Similar work is reported in Chinese patent ZL 201710891621.7. 2 O 3 / Boron-doped gC 3 N 4 It can degrade 97.5% of methyl orange within 120 minutes.
[0007] However, to date, no 2 O 3 and gC 3 N 5 Any reports on materials, preparation methods and applications for composite heterojunction construction.
[0008] In view of the above background and research status, the present invention is proposed. Summary of the invention
[0009] The object of the present invention is to provide a 2 O 3 / gC 3 N 5 A method for preparing heterojunction materials, which uses a hydrothermal method and a high-temperature calcination method, has a simple preparation process and low cost. 2 O 3 and gC 3 N 5 The dislocated band structure between them forms a heterojunction, constructs the transmission space of photogenerated carriers, and promotes the efficient separation of photogenerated electrons and holes. 3 N 5 The efficient visible light response characteristics expand the utilization rate of light by the heterojunction, ultimately achieving a significant improvement in photocatalytic activity.
[0010] Another object of the present invention is to provide an 2 O 3 / gC 3 N 5 Application of heterojunction materials in fields such as removal of environmental pollutants.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] In a first aspect, the present invention provides an In 2 O 3 / gC 3 N 5The preparation method of the heterojunction material comprises the following steps: weighing indium salt, oxalic acid and sodium hydroxide, dissolving and stirring in a beaker, and then transferring to a hydrothermal kettle for reaction; washing the obtained precipitate to remove impurities, and then drying to obtain an intermediate product; adding the intermediate product and 3-amino-1,2,4-triazole into a mortar, grinding and mixing, and then transferring to a crucible, placing in a muffle furnace for roasting to obtain In 2 O 3 / gC 3 N 5 Heterojunction materials.
[0013] The molar ratio of the hydroxide in the sodium hydroxide to the molar ratio of the indium in the indium salt is (3-4):1.
[0014] The molar ratio of the oxalic acid to the hydroxide in the sodium hydroxide is 1:5.
[0015] The mass ratio of the intermediate product to 3-amino-1,2,4-triazole is (0.1~1):1.
[0016] The indium salt is one of nitrate, chloride and sulfate.
[0017] In some embodiments, the reaction temperature of the hydrothermal reactor is 140-180° C., and the reaction time is 24-48 hours.
[0018] In some embodiments, the calcination temperature of the muffle furnace is 500-520° C., and the calcination time is 2-4 hours.
[0019] In a second aspect, the present invention provides an In prepared by the above preparation method. 2 O 3 / gC 3 N 5 Application of heterojunction materials in fields such as removal of environmental pollutants.
[0020] The environmental pollutant includes at least one of rhodamine B, methylene blue, and methyl orange dyes.
[0021] As a preferred embodiment, an In 2 O 3 / gC 3 N 5 The preparation method of the heterojunction material comprises the following steps: weighing indium salt, oxalic acid and sodium hydroxide, dissolving and stirring in a beaker, and then transferring to a hydrothermal kettle for reaction; washing the obtained precipitate to remove impurities, and then drying to obtain an intermediate product; adding the intermediate product and 3-amino-1,2,4-triazole into a mortar, grinding and mixing, and then transferring to a crucible, placing in a muffle furnace for roasting to obtain In 2 O 3 / gC 3 N 5 Heterojunction materials.
[0022] Wherein, in this step, the molar ratio of the hydroxide ion in the sodium hydroxide to the molar ratio of the indium in the indium salt is 4:1, and the molar ratio of the hydroxide ion in the oxalic acid to the sodium hydroxide is 1:5.
[0023] Wherein, in this step, the mass ratio of the intermediate product to 3-amino-1,2,4-triazole is 0.2:1.
[0024] Wherein, in this step, the reaction temperature of the hydrothermal kettle is 180° C. and the reaction time is 24 hours.
[0025] Wherein, in this step, the roasting temperature of the muffle furnace is 520° C., and the roasting time is 3 hours.
[0026] The technical solution provided by the present invention has the following beneficial effects: the present invention adopts a hydrothermal method and a high-temperature roasting method, the preparation process is simple, and the cost is low. 2 O 3 and gC 3 N 5 The dislocation band structure between them forms a heterojunction, constructs the transmission space of photogenerated carriers, and promotes the efficient separation of photogenerated electrons and holes. 3 N 5 The efficient visible light response characteristics expand the utilization rate of light by the heterojunction, ultimately achieving a significant improvement in photocatalytic activity, especially the efficient removal of environmental pollutants such as rhodamine B, methylene blue, methyl orange, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The XRD diagrams of the intermediate product and product obtained in Example 1 of the present invention and the products obtained in Comparative Examples 1 and 2 are shown.
[0028] Figure 2 This is a TEM image of the product obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0031] The reagents and raw materials used in the present invention are shown in Table 1 below: Table 1 Reagents and raw materials used in the present invention Reagent name Molecular formula Specification Manufacturer (Origin) Indium nitrate <![CDATA[InN 3 THE 9 .xH 2 The]]> Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. oxalic acid <![CDATA[C 2 H 2 O 4 ]]> Analytical grade Sinopharm Chemical Reagent Co., Ltd. Sodium hydroxide NaOH Analytical grade Sinopharm Chemical Reagent Co., Ltd. 3-Amino-1,2,4-triazole <![CDATA[C 2 H 4 N 4 ]]> Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. Deionized water <![CDATA[H 2 The]]> <![CDATA[S<5 μs·cm -1 ]]> Hangzhou Wahaha Group Co., Ltd. Example 1
[0032] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times, and vacuum dry to obtain an intermediate product. Weigh 0.4 g of the intermediate product and 2 g of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain In. 2 O 3 / gC 3 N 5 Heterojunction materials.
[0033] Take the prepared In 2 O 3 / gC 3 N 5 100 mg of heterojunction material was placed in a beaker containing 100 ml of 10 mg / L rhodamine B solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-watt xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 99.3%. Example 2
[0034] Accurately weigh 0.01 mol of indium nitrate, 0.006 mol of oxalic acid, and 0.03 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 160°C for 48 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 0.2 g of the intermediate product and 2 g of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 500°C in a muffle furnace for 2 hours to obtain In 2 O 3 / gC 3 N 5 Heterojunction materials.
[0035] Take the prepared In 2 O 3 / gC 3 N 5100 mg of the heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L methylene blue solution, subjected to ultrasonic treatment for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 664 nm was measured by a UV-visible spectrophotometer. The degradation rate of methylene blue was calculated to be 93.4%. Example 3
[0036] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 2 grams of the intermediate product and 2 grams of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain In. 2 O 3 / gC 3 N 5 Heterojunction materials.
[0037] Take the prepared In 2 O 3 / gC 3 N 5 100 mg of heterojunction material was placed in a beaker containing 100 ml of 10 mg / L methyl orange solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 60 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 460 nm was measured by a UV-visible spectrophotometer. The degradation rate of methyl orange was calculated to be 85.6%. Example 4
[0038] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times, and vacuum dry to obtain an intermediate product. Weigh 0.4 g of the intermediate product and 2 g of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain In. 2 O 3 / gC 3 N 5 Heterojunction materials.
[0039] Take the prepared In 2 O 3 / gC 3 N 5 100 mg of the heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L methylene blue solution, subjected to ultrasonic treatment for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 664 nm was measured by a UV-visible spectrophotometer. The degradation rate of methylene blue was calculated to be 97.3%. Example 5
[0040] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times, and vacuum dry to obtain an intermediate product. Weigh 0.4 g of the intermediate product and 2 g of 3-amino-1,2,4-triazole, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain In. 2 O 3 / gC 3 N 5 Heterojunction materials.
[0041] Take the prepared In 2 O 3 / gC 3 N 5 100 mg of heterojunction material was placed in a beaker containing 100 ml of 10 mg / L methyl orange solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 60 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 460 nm was measured by a UV-visible spectrophotometer. The degradation rate of methyl orange was calculated to be 90.5%. Comparative Example 1
[0042] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times each, and vacuum dry to obtain an intermediate product. Weigh 2 grams of the intermediate product and roast it in a muffle furnace at 520°C for 3 hours to obtain In 2 O 3 monomer.
[0043] Take the prepared In 2 O 3100 mg of monomer was placed in a beaker containing 100 ml of 10 mg / L rhodamine B solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 46.2%. Comparative Example 2
[0044] Accurately weigh 2 g of 3-amino-1,2,4-triazole and calcine it in a muffle furnace at 520 °C for 3 hours to obtain gC 3 N 5 monomer.
[0045] Take the prepared gC 3 N 5 100 mg of monomer was placed in a beaker containing 100 ml of 10 mg / L rhodamine B solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 55.9%. Comparative Example 3
[0046] Accurately weigh 0.01 mol of indium nitrate, 0.008 mol of oxalic acid, and 0.04 mol of sodium hydroxide in a 100 ml beaker, add 80 ml of deionized water, continue stirring for 30 minutes after dissolving, transfer to a 100 ml hydrothermal kettle, react at 180°C for 24 hours, wash the obtained precipitate with water and alcohol for 3 times, and vacuum dry to obtain an intermediate product. Weigh 0.4 g of the intermediate product and 2 g of melamine, add them to a mortar, grind and mix, transfer to a crucible, and roast at 520°C in a muffle furnace for 3 hours to obtain In. 2 O 3 / gC 3 N 4 Heterojunction materials.
[0047] Take the prepared In 2 O 3 / gC 3 N 4 100 mg of heterojunction material was placed in a beaker containing 100 ml of 10 mg / L rhodamine B solution, ultrasonically treated for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 30 minutes with a 300-watt xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 85.1%.
[0048] It can be seen from Comparative Examples 1 and 2 that the prepared In2 O 3 Monomer and gC 3 N 5 Monomer material is more 2 O 3 / gC 3 N 5 The degradation effect of heterojunction materials on Rhodamine B decreased significantly under the same conditions, which is mainly due to the fact that In 2 O 3 Monomer and gC 3 N 5 The recombination probability of photogenerated electrons and holes in monomer materials is high, and sufficient photogenerated carriers required for efficient photocatalytic reactions are not generated.
[0049] It can be seen from Comparative Example 3 that the preparation of In 2 O 3 / gC 3 N 4 Heterojunction materials are more 2 O 3 / gC 3 N 5 The degradation effect of heterojunction materials on rhodamine B also decreased significantly under the same conditions, which is mainly due to the fact that gC 3 N 4 The band gap of gC is large, which affects the effective separation of photogenerated carriers. 3 N 5 The material's absorption range of visible light is expanded, and the utilization rate of visible light is increased. In 2 O 3 / gC 3 N 5 Characterization of heterojunction materials
[0050] The present invention uses a D8 Advance X-ray diffractometer from Bruker Spectroscopy Instruments of Germany to analyze the intermediate product prepared in Example 1, In 2 O 3 / gC 3 N 5 Heterojunction materials, In prepared in Comparative Example 1 and Comparative Example 2, respectively 2 O 3 and gC 3 N 5 The product was subjected to XRD analysis and the results were as follows Figure 1 As shown, the test conditions are: Cu target Kα line, λ = 0.15406nm, 2θ is 10°~70°, and the scanning speed is 5(°) / min. Figure 1 The intermediate product of Example 1 is In(OH) 3The diffraction peaks at 22.3, 31.7, 35.6, 39.1, 45.5, 51.2, 56.5 and 66.3 degrees respectively correspond to the pure body-centered cubic phase In(OH) 3 (200), (220), (013), (222), (400), (420), (422) and (440) planes (PDF card 85-1338), In(OH) 3 It has high purity and crystallinity. Figure 1 The product of Comparative Example 1 is In 2 O 3 , the diffraction peaks at 21.3, 30.6, 35.5, 51.0° and 60.6° respectively correspond to In 2 O 3 (PDF card 71-2195) with (211), (222), (400), (440) and (662) planes, space group la-3, a=b=c=10.117. Figure 1 The product of Comparative Example 2 is gC 3 N 5 , the diffraction peaks at 12.8° and 27.5°, respectively, correspond to the (100) and (002) crystal planes. In the XRD spectrum of the product of Example 1, the product In of Comparative Example 1 2 O 3 And the product gC of Comparative Example 2 3 N 5 All diffraction peaks of can be observed, and the intensity is reduced, indicating that the product is In 2 O 3 and gC 3 N 5 They are composited and retain their respective crystal structures.
[0051] The present invention uses a high-resolution field emission transmission electron microscope JEM-2100F produced by JEOL Ltd. to test the In obtained in Example 1. 2 O 3 / gC 3 N 4 The microstructure of the heterojunction material is shown in the following photos. Figure 2 shown. Figure 2 It can be seen that In 2 O 3 / gC 3 N 5 Heterojunction materials mainly include gC with a layered structure 3 N 5 and In with a cubic structure 2 O 3The two are closely combined, which makes it possible for the efficient transmission of photogenerated carriers.
[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an In2O3 / g-C3N5 heterojunction material, characterized in that: The invention comprises the following steps: weighing indium salt, oxalic acid and sodium hydroxide, dissolving and stirring in a beaker, and then transferring to a hydrothermal kettle for reaction; washing the obtained precipitate to remove impurities, and then drying to obtain an intermediate product; adding the intermediate product and 3-amino-1,2,4-triazole into a mortar, grinding and mixing, and then transferring to a crucible; and placing the mixture in a muffle furnace for roasting to obtain an In2O3 / g-C3N5 heterojunction material, wherein the molar ratio of the number of hydroxide in the sodium hydroxide to the molar number of indium in the indium salt is (3-4):1, the molar ratio of the hydroxide in the oxalic acid to the sodium hydroxide is 1:5, the mass ratio of the intermediate product to 3-amino-1,2,4-triazole is (0.1-1):1, the reaction temperature of the hydrothermal kettle is 140-180°C, the reaction time is 24-48 hours, the roasting temperature of the muffle furnace is 500-520°C, and the roasting time is 2-4 hours.
2. The preparation method according to claim 1, characterized in that: The indium salt is one of nitrate, chloride and sulfate.
3. Use of an In2O3 / g-C3N5 heterojunction material obtained by the preparation method described in any one of claims 1 to 2 in removing environmental pollutants.
4. The use according to claim 3, characterized in that: The environmental pollutant includes at least one of rhodamine B, methylene blue, and methyl orange dyes.
Citation Information
Patent Citations
Process for preparing In2O3 nano-wire
CN101148266A
Preparation method of nitrogen-rich graphite phase carbon nitride / silver meta-vanadate composite photocatalyst
CN112495420A
Cadmium sulfide / indium oxide / phosphorus oxide doped carbon nitride ternary composite material as well as preparation method and application thereof
CN114602528A
Preparation method of mixed crystal phase WO3atg-C3N5 composite photocatalyst
CN114904547A
Pt / In2O3 / g-C3N4 composite nano photocatalytic material and preparation method thereof
CN118477670A